2017
DOI: 10.1186/s12971-017-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of e-cigarette exposure incidents reported to 10 European Poison Centers: a retrospective data analysis

Abstract: BackgroundThe use of e-cigarettes has increased during the past few years. Exposure to e-cigarette liquids, whether intentional or accidental, may lead to adverse events our aim was to assess factors associated with e-cigarette exposures across European Union Member States (EU MS).MethodsA retrospective analysis of exposures associated with e-cigarettes reported to national poison centers was performed covering incidents from 2012 to March 2015 from 10 EU MS. De-identified and anonymous raw data was acquired.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 13 publications
3
25
0
1
Order By: Relevance
“…This study prospectively described e-cigarette exposures reported to a regional Poison Center over a 42-month period. Current knowledge of e-cigarette exposures and their associated toxicity is based on case reports, small case series, and retrospective poison center data [2,3,7,[9][10][11]. Several published reports have described e-cigarette exposures causing topical irritation [8,12], GI symptoms [5,7,13,14], myocardial infarction [15], and severe nicotine toxicity manifesting as respiratory arrest [1,7,16], and even death [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study prospectively described e-cigarette exposures reported to a regional Poison Center over a 42-month period. Current knowledge of e-cigarette exposures and their associated toxicity is based on case reports, small case series, and retrospective poison center data [2,3,7,[9][10][11]. Several published reports have described e-cigarette exposures causing topical irritation [8,12], GI symptoms [5,7,13,14], myocardial infarction [15], and severe nicotine toxicity manifesting as respiratory arrest [1,7,16], and even death [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of exposures in these datasets resulted in minor or no effects [11,23]. Commonly reported adverse effects were vomiting, nausea, eye irritation, and dizziness [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…In Texas, Poison Centers received 225 calls between 2009-2014 [165], while in Utah 52 cases were reported to have been poisoned by a synthetic cannabinoid in 2017-2018 [166]. Between 2012-2015, 277 calls were made to 10 European Countries' Poison Centers [12], while in the UK, between 2008-2016, 278 calls were made to the National Poisons Information Service (NPIS) regarding children under 16 years old [167]. Between 2012-2018, 148 cases of acute exposure to e-cigarettes were reported to Czech Toxicological Information Centre [69].…”
Section: Poisoningmentioning
confidence: 99%
“…The first case of e-cigarette-related lung injury was a case of lipoid pneumonia published in 2012 [11], furthermore from 2012 to 2015, 277 incidents of poisoning have been reported to National Poison Centers of 10 EU MS [12] and similarly increased poisoning incidents have been reported by US poison centers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Es vergiften sich v. a. Kinder bis zum Alter von 5 Jahren infolge einer oralen Aufnahme von Liquids. Diese Vergiftungsgefahr lässt sich durch kindersichere Verpackungen, eine eindeutige Kennzeichnung der Behälter und eine kindersichere Lagerung minimieren [3,8].…”
Section: Schadenspotenzial Der Inhaltsstoffe Des Aerosolsunclassified